Questions of cultural identity - Hall, Stuart; Du Gay, Paul (Sage, 1996)
Why and how do contemporary questions of culture so readily become highly charged questions of identity? The question of cultural identity lies at the heart of current debates in cultural studies and social theory. At issue is whether those identities which defined the social and cultural world of modern societies for so long - distinctive identities of gender, sexuality, race, class and nationality - are in decline, giving rise to new forms of identification and fragmenting the modern individual as a unified subject. Questions of Cultural Identity offers a wide-ranging exploration of this issue. Stuart Hall firstly outlines the reasons why the question of identity is so compelling and yet so problematic. The cast of